Correction: Effects of nitrogen, phosphorus and potassium formula fertilization on the yield and berry quality of blueberry. - Xinyu Zhang; Shuangshuang Li; Xiaoli An; Zejun Song; Yunzheng Zhu; Yi Tan; Xiaolan Guo; Delu Wang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0283137.].